Solubility enhancement of etoricoxib using inclusion complexation with cyclodextrins: formulation of oro dispersible tablets by QbD approach - Mahapatra, Anjan Kumar; Dora, Siddharth; Parida, Sanatan; Bal, Usharani; Jena, Bandana Rani; Lenka, Madhusmita (Creative Pharma Assent, 2024)
Background: The work was intended to enhance etoricoxib's solubility and dissolution rate and then develop oro-dispersible tablets for faster onset of action. Methodology: Inclusion complexes (ICs) of the drug were obtained with β-cyclodextrin (β-CD) and hydroxypropyl β-cyclodextrin (HP β-CD) at ratios of 1:0.125, 1:0.25, 1:0.5, 1:1, and 1:2 (w/w). The selected cyclodextrin at appropriate drug carrier proportion was used to develop oro-dispersible tablets (ODTs) by direct compression, adding crospovidone as a super disintegrant. Phase solubility studies of etoricoxib were carried out by using multiple concentrations of β-cyclodextrin and hydroxypropyl β-cyclodextrin, i.e., 1 %, 2 %, 3 % w/v in distilled water at 37±2°C. Spectroscopic (FT-IR) and thermal analysis (DSC) techniques were employed to identify the drug-carrier interactions. Result: It showed that etoricoxib solubility improves with increasing hydrophilic carrier concentration. The Gibbs free energy values (ΔG˚tr) are consistently negative, showing the solubility of etoricoxib. Significant drug carrier interaction in spectroscopic or thermal analysis was not found. Discussion: The ICs of drugs with β-CD and HP β-CD have successfully addressed the challenges of solubility enhancement and taste masking for etoricoxib. Conclusions: It is observed that the inclusion complexes formed by the kneading method using β-cyclodextrin (β-CD) at a 1:1 ratio and hydroxypropyl β-cyclodextrin (HP β-CD) at a 1:2 ratio can be used to improve dissolution. Hence β-CD (at a 1:1 ratio) is selected for the formulation of oro-dispersible tablets. ODTs offer more patient compliance and an alternative to available conventional tablets.